Cultivar mixtures for the simultaneous management of multiple diseases: tan spot and leaf rust of wheat - Cox, C. M.; Bowden, Robert L.; Fritz, A. K.; Dendy, S. P.; Heer, William F.; Garrett, Karen A. (My University, 2007)
Because of differences in life histories between Puccinia triticina, a highly specialized, polycyclic, windborne pathogen with a shallow dispersal gradient, and Pyrenophora tritici-repentis, a residue-borne pathogen with a steep dispersal gradient, wheat mixtures are expected to be more effective at controlling leaf rust than tan spot. The objectives of this research were to determine the effect of two-cultivar mixtures with varying proportions and different pathogen resistance profiles on the severity of tan spot and leaf rust, to evaluate yield of the mixtures in the presence or absence of disease, and to directly compare the relative effectiveness of cultivar mixing for tan spot versus leaf rust. In a field experiment at two sites in Kansas over two growing seasons, winter wheat cvs. Jagger and 2145, which have differential resistance reactions to leaf rust and tan spot, each were planted in proportions of 0.25, 0.50, 0.75, and 1.00. Plots were inoculated with each pathogen alone, both pathogens, treated with a fungicide, or exposed to ambient conditions. For both diseases for all siteyears, severity decreased substantially on the susceptible cultivar as the proportion of that cultivar decreased in mixture. Mixtures were significantly more effective at reducing leaf rust than tan spot in three of four site-years. Mixtures generally yielded the same as the weighted mean of components in monoculture although, in two of three site-years, at least one fungicide-treated and one diseased mixture each yielded higher than expected values. Although this particular mixture produced only modest yield benefits, the potential for simultaneous reductions in tan spot and leaf rust was demonstrated.
Citation: Cox, C., . . . & Heer, W. (2004). Cultivar Mixtures for the Simultaneous Management of Multiple Diseases: Tan Spot and Leaf Rust of Wheat. Phytopathology, 94(9), 961-969. https://doi.org/10.1094/PHYTO.2004.94.9.96
Keywords: Tan spot; Leaf rust; Host diversity; Plant diversity; Polyculture; Variety mixture; Frequency-dependent effects